Gut epithelial impairment, microbial translocation and immune system activation in inflammatory bowel disease–associated spondyloarthritis. (23rd May 2020) - Luchetti, Michele Maria; Ciccia, Francesco; Avellini, Chiara; Benfaremo, Devis; Rizzo, Aroldo; Spadoni, Tatiana; Svegliati, Silvia; Marzioni, Daniela; Santinelli, Alfredo; Costantini, Andrea; Viola, Nadia; Berretta, Antonella; et al.
Abstract: Objectives: Gut microbiota has been widely reported to be involved in systemic inflammation through microbial translocation and T cell activation in several diseases. In this work we aimed to investigate bacterial infiltration and epithelial impairment in the gut of patients with IBD-associated SpA (SpA-IBD), as well as the relationship of microbial translocation with immune system activation and their putative role in the pathogenesis of joint inflammation in IBD patients. Methods: Tight-junction proteins (TJPs) occludin and claudin-1/-4 and bacteria were assessed by real-time PCR analysis and immunohistochemical staining of the ileum. Intestinal fatty acid binding protein (I-FABP), lipopolysaccharides (LPS), soluble CD14 (sCD14), sclerostin and anti-sclerostin antibodies (anti-sclerostin-IgG) were assayed with ELISAs and peripheral mononuclear blood cells with flow cytometry. LPS and sCD14 were used in vitro to stimulate a human osteoblast cell line. Results: Compared with IBD, ileal samples from SpA-IBD patients showed bacterial infiltration, epithelial damage and downregulation of TJPs. In sera, they showed higher serum levels of I-FABP, LPS, sCD14 (the latter correlating with sclerostin and anti-sclerostin-IgG) and higher CD80 + /CD163 + and lower CD14 + mononuclear cells. In vitro experiments demonstrated that only the LPS and sCD14 synergic action downregulates sclerostin expression in osteoblast cells. Conclusion: SpA-IBD patients are characterized by gut epithelium impairment with consequent translocation of microbial products into the bloodstream, immune system activation and an increase of specific soluble biomarkers. These findings suggest that gut dysbiosis could be involved in the pathogenesis of SpA-IBD and it could hopefully prompt the use of these biomarkers in the follow-up and management of IBD patients.